Sociological View on the Institution of the Market - Stoilova, Vyara (Research Papers, 2016)
This paper provides a sociological point of view on the institution of the market in terms of the social cohesion which it builds. The specifics of this cohesion is determined by the principle of the competition as a basic mechanism for coordination and cooperation of the activity of the market actors as well as by the ambivalence of the social role "a market actor". The free choice which results from the competition, enables the market actors to pursue their own interests and determines the spontaneity of the market exchanges - “spontaneous order” (Hayek) of the relationships of the market actors. The ambivalence of the social role "a market actor", which is expressed in the fact that its performer embodies both sides of the market exchange (buyer and seller, although at different times), determines the rationality of the market actor’s behavior. The coercive nature of this social role in terms of the access to rights of ownership of certain goods, including money, as well as the increasing role of the market in a number of non-economic activities in society, limit the overall ensemble role of man as an expression of the totality of relationships which he manages to build with others.